Effect of Compressive Behaviours of Tail Salt Filling Materials on Roof Deformation in Potash Mine. (17th June 2021) - Wang, Jiaqi; Zhang, Qiang; Li, Meng; Liu, Hengfeng; Zhu, Cunli
Abstract : To resolve the problem of top mine instability and the consequent ecological damage caused by different grades of ore deposits in the layered mining process, layered filling-pillar-mining-displacement method (LFPMD) is proposed using a potash mine as an example. Based on the operation principles of the tail salt filling system, the mechanical behaviours of the tail salt under initial tamping and overburden loading were obtained through compaction tests in the laboratory. In addition, the mining-filling mass ratio of tail salt was derived. Based on the mining geological conditions of a potash mine in Laos and the compaction characteristics of tail salt, a mechanical model of top control by tail salt and a numerical model of top control by the pillars were established to discuss the stability of the upper-layer top mine and the lower-layer top mine. It was found that when the elastic foundation coefficient of the tail salt is greater than 550 MN·m −3, and the width of the retained pillars is 10 m, stability of the upper layer and the lower layer can be guaranteed. The results revealed that the LFPMD method can ensure stability of the overburden in the stope and reduce environmental damage while treating tail salt underground.